Identification of Massoia Lactone and its Hydroxy-derivative from Kabatiella caulivora, an Endophyte of the Terrestrial Plant Alyxia reinwardtii - Laili, Izzatul; Gunarso, Sri; Wathan, Nashrul; Sugijanto, Noor Erma; Indrayanto, Gunawan (UI Scholars Hub, 2017)
Massoia lactone (1) and its derivative, 3,5-dihydroxydecanoic acid-d-lactone (2), were identified from an ethyl acetate extract of the endophytic fungus Kabatiella caulivora, isolated from its host Alyxia reinwardtii. The compounds were identified by GC-MS. To the best of our knowledge, this is the first report of the identification of massoia lactone and its derivative from the endophytic K. caulivora fungus.